2018
DOI: 10.1007/s11274-018-2469-9
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of benzo[a]pyrene by the thermophilic bacterium Bacillus licheniformis M2-7

Abstract: Benzo[a]pyrene (BaP) is recognized as a potentially carcinogenic and mutagenic hydrocarbon, and thus, its removal from the environment is a priority. The use of thermophilic bacteria capable of biodegrading or biotransforming this compound to less toxic forms has been explored in recent decades, since it provides advantages compared to mesophilic organisms. This study assessed the biotransformation of BaP by the thermophilic bacterium Bacillus licheniformis M2-7. Our analysis of the biotransformation process m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 39 publications
0
12
0
4
Order By: Relevance
“…only if hexane was added as a growth substrate, a classical approach of cometabolism [6,38]. So far, only one bacterial strain, the thermophilic Bacillus licheniformis M2-7, has been reported to degrade BaP as a sole substrate at 50 o C [22]. In the current work, the investigation on the temperature effect has shown the optimum range of 35-40 o C. Bacteria of Staphyloccocus genus are known to be halotolerant, with an optimum range of 7.5-10% NaCl [39,40].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…only if hexane was added as a growth substrate, a classical approach of cometabolism [6,38]. So far, only one bacterial strain, the thermophilic Bacillus licheniformis M2-7, has been reported to degrade BaP as a sole substrate at 50 o C [22]. In the current work, the investigation on the temperature effect has shown the optimum range of 35-40 o C. Bacteria of Staphyloccocus genus are known to be halotolerant, with an optimum range of 7.5-10% NaCl [39,40].…”
Section: Plos Onementioning
confidence: 99%
“…Several studies have been dedicated on the degradation of PAHs by active non-halophilic microorganisms [11][12][13]. Although most of this work has been devoted to PAHs containing up to four fused benzene rings, nevertheless, few microbes have been reported to degrade BaP in non-halophilic conditions, they include Sphingomonas yanoikuyae JA, Mycobacterium sp., Mycobacterium vanbaalenii, Stenotrophomonas maltophilia, Novosphingobium pentaromativorans, Mesoflavibacter zeaxanthinifaciens, Ochrobactrum sp., Bacillus licheniformis and Bacillus subtilis [14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, G. stearothermophilus strain A-2 was isolated from produced water from Dagang petroleum reservoir, China at a temperature of 73 o C. Further studies showed that this strain could degrade NAPH, methylated PHEN, FLR, benzo[b]fluorenes and long-chain alkanes (nC22-nC33).However, shorter chains (nC14-nC21) were not efficiently degraded. In addition, this strain had a strong surface hydrophobicity and produced a bioemulsifier, making it an ideal strain for of the catechol dioxygenase enzyme, a clear illustration of the ability of this strain to convert BZP to aliphatic derivatives[66] [ST35]. Geobacillus are the most dominant PHDTAs Table 1shows, a total of 49 different strains of thermophilic bacteria and one archaea (S.…”
mentioning
confidence: 99%
“…In another recent study, a strain of Bacillus licheniformis M2-7 was isolated from an inoculum from a hot spring in Mexico, and was proved to degrade BZP. Further studies have led to the identification of the MAH phthalic acid as a BZP metabolite, and the characterization of the catechol dioxygenase enzyme, a clear illustration of the ability of this strain to convert BZP to aliphatic derivatives [66] (ST35).…”
Section: Summary Of Work On Phdtmentioning
confidence: 99%